Asymptomatic Papulo-nodules Localized to One Finger - Rambhia, Kinjal D (Indian J Dermatol, 2015)
Subcutaneous or deep granuloma annulare is a benign asymptomatic condition characterized by firm asymptomatic nodules in deep subcutaneous tissues that may be associated with intradermal lesions. A 53-year-old female presented with asymptomatic skin-colored, firm nodules over the right ring finger. Histopathology revealed a palisading granuloma with central degenerated collagen and mucin deposition in the dermis suggestive of granuloma annulare. Isolated and unilateral involvement of a single digit with clusters of nodules of subcutaneous granuloma annulare (GA) in an adult is rare and differentiation from its simulator rheumatoid nodule is essential.